Morphological characteristics of the surgical neck region in the proximal humerus at different ages - Jialiang Guo; Yali Zhou; Meishuang Shang; Wei Chen; Zhiyong Hou; Yingze Zhang; Weichong Dong (European Journal of Medical Research, 2022)
Abstract Background The objective of the study was to demonstrate the cortical thickness character in the humeral surgical neck region using 3D cortical bone mapping technique and try to illustrate its morphological changes with age. Material and methods Normal individuals, including 11 volunteers younger than 18 years, 87 adult men and 46 adult women, were enrolled. The cortical thickness and height of the surgical neck region was measured with Mimic and 3 Matic software. The height of the region was compared and measured. People with an age of 18–30 years was identified as Group I, people in 31–40 years as Group II, people in 41–50 years as Group III, people in 51–60 years as Group IV, and Group V including people ≥ 61 years. Results Compared with the baseline Group I, cortical thickness was significantly decreased by 0.52 mm (P = 0.006) in Group III, by 0.76 mm (P < 0.001) in Group IV, and by 0.77 mm (P < 0.001) in Group V. Age moderately predicted cortical thickness with r = −0.5481. The height of the cortical change region was significantly decreased by 2.25 mm (P = 0.007) in Group II, by 2.98 mm (P < 0.001) in Group III, and by 2.07 mm (P = 0.02) in Group IV. However, no significant decrease was illustrated in Group V (0.57 mm) (P = 0.891). The relation between age and the height of the cortical thickness change region was nonlinear. Conclusions This study identified an obvious decrease in cortical thickness with aging, and the height was curve fitted with aging in surgical neck region.